THE INFLUENCE OF DIVIDEND POLICY, CAPITAL STRUCTURE, AND PROFITABILITY ON FIRM VALUE (A Case Study of Non-Cyclical Consumer Sector Companies Listed on the Indonesia Stock Exchange in 2021–2023) - Ni Kadek Diah Manika Sari Dwimahyu; Ica Rika Candraningrat (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Firm value reflects a company's past performance, current condition, and future prospects. A high firm value indicates not only investor confidence in the company’s financial performance but also the total assets owned by the company, serving as a reflection of shareholder wealth. Firm value can be influenced by several factors, including dividend policy, capital structure, and profitability. This study aims to examine the influence of dividend policy, capital structure, and profitability on firm value. The research was conducted on companies listed consecutively in the Consumer Non-Cyclicals sector on the Indonesia Stock Exchange (IDX) during the 2021–2023 period and that consistently distributed dividends throughout the same period. The study population consisted of 40 companies. The sampling technique employed was probability sampling using the simple random sampling method. The sample size was determined using Slovin’s formula, resulting in 36 companies. With an observation period of three years, the total number of observations was 108. The statistical analysis results indicate that dividend policy, capital structure, and profitability have a positive and significant effect on firm value.